The Arab-American Press And The Arab World; News Coverage In Al-Dayan And Al-Dalil - Alhourani, Motaz Abdullah (Kansas State University, 1993)
This Master's report deals with the news coverage of the Arab world as well as the Arab-American community in two of the early Arabiclanguage newspapers published in the United States. Al-Bayan and AJ:. llalil first appeared at the beginning of the twentieth century. Like most Arabic-language newspapers at the time, they were supported by certain religious sects which tried to advance their objectives and ideologies through these newspapers. Al-Bayan and Al-Datil discussed many issues related to both the Arab world and the Arab community. This report tries to shed light on some of these issues, such as Ottoman control of the Arab World, European control of the Arab world, Arab identity, the Zionist threat to Ottoman rule, and activities of the Arab-American community. As far as the Arab world was concerned, both newspapers supported Ottoman occupation at the beginning. Al-Datil moved on to support European control of the Arab world, while Al-Dayan shifted its position to advocate Arab independence, and then shifted back to supporting the Ottomans when it realized that Arab independence was unattainable. As far as the Arab-American community was concerned, Al-Dayan was the voice of Droze and Al-Datil was the voice of Christians in the United States. When discussing the Palestinian problem, however, Al:. Bayap tried to represent the Arab-American community in general.